Public Transportation Passengers Accounting at University by IoT Device - Vieira, Daniel Filipe; Guillardi Junior, Hildo [UNESP]; IEEE (Ieee, 2022)
Public transport are alternatives for people daily locomotion due their economic and environmental factor, mainly in large cities. Acknowledgement about the vehicles use and people flux are mandatory to achieve better cost efficiency in the different modes of transport. In this scenario, a real-time people flux acquisition system make possible optimized planning and operation by identification of peak and daily demands. A good way to get such information is through automatic passenger counters associated with Global Navigation Satellite System which allows to geographical cross-reference the demand. This work describes the development and validation of the hardware and firmware of a low-cost Internet of Things solution for passengers boarding and alighting counting on buses from the internal public transportation system at the University of Campinas. The developed low cost device uses infrared sensors to detect people boarding/alighting and an ESP32 microcontroller to accumulate and send the data through Message Queue Telemetry Transport communication under GPRS wireless network.
Keywords: Internet of Things; Message Queue Telemetry Transport; Public Transportation